UPAYA HUKUM DALAM DALUWARSANYA HAK UNTUK MENUNTUT ATAS PEMALSUAN TANDA TANGAN PADA SURAT PERMOHONAN PEMBUATAN PASPOR RI DI KANTOR IMIGRASI KELAS I SAMARINDA - Tri Suci Suprianawati (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSRACTBook of the Law Criminal Law (KUHP) has set a certain period of time on the subject of prosecution, can be expired by law.The provisions in Article 78 KUHP actually set expiration rights of criminal prosecution, but should also be linked with the right to enforce penalties. Time of death of the right to run a longer sentence than the death of a criminal prosecution the right of the defendant in error for sure.The offenses of counterfeiting as governed by Article 263 KUHP was in fact a criminal act that should be done deliberately up to declare a person charged with the crime of forgery was proven, the public prosecutor and the judge had to prove the defendant's will to act falsely or falsify letter. The existence of the defendant's intent to use the letter as a letter of their own genuine and not faked or to make others use a letter that he created artificially, required the presence of the defendant's knowledge of the use of the letter that he had made false or that it is fake it can cause loss.